AL-QAṬ’ WA AL-ẒANN ‘INDA IBRĀHĪM ḤUSAYN: Namūdhaj Tajdīd al-Sharī‘ah al-Islāmīyah fī Indūnīsīyā Naḥwa al-Fiqh al-Indūnīsīyī al-Shāmil (JOURNAL OF INDONESIAN ISLAM, 2020)
Amidst the rise of textual and literal approach of Islam, the spirit and the purpose of Islamic law are often overlooked. The application of Islamic law should be able to go hand in hand with the changing dynamics of the times. As many novel legal issues take place, Muslim jurists must respond with adequate solution bearing in mind the spirit and purposes of Islamic law for the welfare of human being. This article discusses Ibrahim Hosen, an Indonesia Muslim jurist of the 1980s who upheld this principle in his fatwas. As the chairman of fatwa issuing body of Indonesian Ulama council at the time, he was in the forefront of delicate situation of positioning Islamic law in the modern context. His idea of “mem-fiqh-kan yang qath’i” which means redefining the absolute aspect of Islamic jurisprudence created considerable impact on the application of Islamic law in Indonesia. It did make him a controversial muslim jurist, aspecially after he issued several controversial legal opinions (fatwa), namely the lawfulness of national lottery and lawfulness of beer on which the majority of Indonesian Muslim jurists considered as gambling and liquor.